Hypercapnia-Induced Amelioration of the Intestinal Microvascular Oxygenation in Sepsis is Independent of the Endogenous Sympathetic Nervous System. Issue 3 (March 2018) - Schulz, Jan; Schöneborn, Sabrina; Vollmer, Christian; Truse, Richard; Herminghaus, Anna; Bauer, Inge; Beck, Christopher; Picker, Olaf
ABSTRACT: Introduction: Insufficient microvascular oxygenation (μHBO2 ) of the intestinal mucosa worsens outcome of septic patients. Hypercapnia ameliorates μHBO2, mediated via endogenous vasopressin release. Under physiological conditions, blockade of the endogenous sympathetic nervous system abolishes this protective effect of hypercapnia. The aim of our study was therefore to evaluate the role of the endogenous sympathetic nervous system during hypercapnia on intestinal μHBO2 under septic conditions. Methods: We randomized 80 male Wistar rats into eight groups. Sepsis was induced via colon ascendens stent peritonitis. The animals were subjected to 120 min of normocapnic (pCO2 35 mm Hg–45 mm Hg) or moderate hypercapnic (pCO2 65 mm Hg–75 mm Hg) ventilation 24 h after surgery. Animals received sympathetic blockade (hexamethonium 15 mg · kg −1 (bolus) followed by 15 mg · kg −1 · h −1 (infusion) intravenously) or the same volume as vehicle (NaCl 0.9%). Microcirculatory oxygenation (μHBO2 ) and perfusion (μflow) were recorded using tissue reflectance spectrophotometry and laser Doppler. Results: In septic animals, μHBO2 decreased during normocapnia (−8.9 ± 4%) and increased during hypercapnia (+7.8 ± 7.5%). The additional application of hexamethonium did not influence these effects. μHBO2 declined in normocapnic septic animals treated with hexamethonium similar to normocapnia alone (−6.1 ± 5.4%) and increased in hypercapnic animals treated with hexamethonium similar to hypercapnia alone (+7.9 ± 11.7%). Furthermore, hypercapnic ventilation ameliorated microcirculatory perfusion (μflow) irrespective of whether animals received hexamethonium (from 113 ± 54 [AU] to 206 ± 87 [AU]) or vehicle (from 97 ± 37 [AU]–169 ± 52 [AU]). Conclusion: The amelioration of the intestinal microcirculation during hypercapnia in sepsis is independent of the endogenous sympathetic nervous system. Abstract : Supplemental Digital Content is available in the text